Femme [videorecording (Blu-Ray)] - Freeman, Sam; Ng, Choon Ping; Stewart-Jarrett, Nathan, 1985-; Heffernan, Aaron; McCrea, John; Mackay, George (British Broadcasting Corporation, 2022)
Jules' life and career as a drag queen is destroyed by a homophobic attack. But when he re-encounters his attacker, the deeply-closeted Preston, in a gay sauna, he is presented with a chance to exact revenge. Unrecognizable out of his wig and make-up, Jules infiltrates Preston's life, and in doing so, discovers power in a different kind of drag..